2023
DOI: 10.1021/acs.nanolett.3c00169
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Fabrication of Bulk-Insulating Topological Insulator Nanowires for Quantum Devices

Abstract: In a nanowire (NW) of a three-dimensional topological insulator (TI), the quantum confinement of topological surface states leads to a peculiar sub-band structure that is useful for generating Majorana bound states. Top-down fabrication of TINWs from a high-quality thin film would be a scalable technology with great design flexibility, but there has been no report on top-down-fabricated TINWs where the chemical potential can be tuned to the charge neutrality point (CNP). Here we present a top-down fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…In this bulk-insulating nanowire, we observed the characteristic AB-like magnetoresistance oscillations with a period of h/e in parallel magnetic fields stemming from the magnetic flux dependence of the Dirac subbands formed in TI nanowires due to the quantum size effect. 19−22 The phase shift of these oscillations upon gating is commonly observed in bulkinsulating TI nanowires, 21,22,26 and it is also the case here: After subtracting a smooth background from the raw data to obtain ΔR (see the Supporting Information for details), we find oscillations whose phase shifts with V G (Figures 4d−f). Note that the oscillations and the phase shift have considerable irregularity, which points to strong disorder.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…In this bulk-insulating nanowire, we observed the characteristic AB-like magnetoresistance oscillations with a period of h/e in parallel magnetic fields stemming from the magnetic flux dependence of the Dirac subbands formed in TI nanowires due to the quantum size effect. 19−22 The phase shift of these oscillations upon gating is commonly observed in bulkinsulating TI nanowires, 21,22,26 and it is also the case here: After subtracting a smooth background from the raw data to obtain ΔR (see the Supporting Information for details), we find oscillations whose phase shifts with V G (Figures 4d−f). Note that the oscillations and the phase shift have considerable irregularity, which points to strong disorder.…”
Section: Resultssupporting
confidence: 67%
“…In our experiment, we found that the realization of bulk insulation for nanosized structures requires reoptimization of the growth conditions that turned out to depend on the feature size. In the bulk-insulating TI nanowires obtained via SAE, our transport experiments found Aharonov–Bohm (AB)-like magnetoresistance oscillations in magnetic fields applied parallel to the nanowire that are characteristic of the quasi-one-dimensional transport through size-quantized topological surface states, confirming their topological nature.…”
Section: Introductionsupporting
confidence: 53%
“…A ϕe |ω| P(ω) with (ω ir < ω < ω uv ) [64,68]. A ϕe is related to the circumference of the device [69,70], for the device with 2DTI, the circumference can be two orders of magnitude less than traditional SQUID device [71,72]. Therefore, we take A ϕe = 10 −14 ϕ 2 0 for flux noise.…”
Section: Coherent Properties Of the Qubitmentioning
confidence: 99%
“…Moreover, unintentional and intrinsic doping can increase the bulk conductivity of topological insulators, too. To increase a ratio between the surface and bulk states, 2D-films or 1D-nanowires are reasonably applied for the transport measurements [17][18][19][20][21][22]. Besides, the bulk conductivity of solids can be effectively reduced by forming a specific defect structure, if defects act as compensation doping centres, reducing majority carriers content, or modify a band structure in manner, reducing a generation of current carriers [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%